Zabicie ciotki Based on a Novel by Andrzej Bursa - Krolikiewicz, Grzegorz; Ptak, Krzysztof; Cherubin, F. Robert; Kleydysz, Maria; Luczycka, Wanda (Telewizja Kino Polska)
A grotesque fairy tale of fantasies in a 21-year old's mind. First he confessess to a priest about killing his aunt. Then he is sending parcels from the post office. Just when it appears that he is going to be arrested, the aunt appears alive and well from her trip. This time though, he decides to go for it ... [Polish Cinema Database]